Attitudes of footballers of different sports experience to training means of recovery - Smajic, M.; Mihajlovic, I.; Bekvalac, D. (Acta Kinesiologica, 2010)
Training means of sportsmen recovery are considered to be the means (exercises) of training that can be used equally for raising the level of training and the optimal recovery of sportsmen. Various means and methods should be used in order to increase the efficiency of training means of recovery. The dosage and methods of their application should be changed, i.e., their application should always be complex, variable and specific, depending on sorts and the structure of training process. The aim of the research consists of testing and analyzing the attitudes of footballers of different sports experience to training means of recovery. The sample of examinees consists of 120 footballers, of nine different league teams, from the area of the Football Association of Vojvodina, divided into two groups after their experience: I group (62) - 4-8 years of sport experience, II group (58) - 9 - 14 years of sports experience. The sample of variables constitutes a system of 10 items (statements), and each paragraph (statement) contains 5 verbal categories (indicated by -2 to +2). To determine the multivariate and univariant significance of differences between footballers of different sports experience, the multivariate analysis of variance (MANOVA) and the univariant analysis of variance (ANOVA) are applied. Generally, it can be concluded that the footballers of different sports experience differ and do not agree on the confirmation of the proposed items.